Toward Evidence-Based Practice. Issue 5 (September 2021) - Rohan, Annie; Lake, Eileen T.; Ogboenyiya, Anisa A.; Westphaln, Kristi K.
Abstract : Experts suggest how 6 research articles can be used in nursing practice.